Implementation of an app-controlled robotic arm to optimize loading processes in Callao-Peru - Gómez-Huamán, Javier Junior; Castro-Vargas, Cristian (Institute of Advanced Engineering and Science, 2025)
Efficient handling of heavy loads represents a constant challenge for businesses, which traditionally rely on significant numbers of staff, involving considerable financial costs and occupational health risks exacerbated by the need for specialized infrastructure. Despite technological limitations and structural deficiencies, this solution has prevailed in practice. However, engineering has responded with innovations aimed at optimizing these processes. In this context, the study proposes to adopt an approach based on implementing a robotic arm supported by technologies such as Arduino, Bluetooth devices, servo motors, and remote-control software developed in App Inventor. This approach promises not only the reduction of labor costs and the improvement of job security but also a positive impact in social and economic terms. A preliminary prototype is presented that validates the basic functionality of the proposed robotic arm. This study presents a technically and economically viable alternative for managing heavy loads in enterprise environments, reducing dependence on a large workforce, and improving operational efficiency.